LQ

Tìm x

( x - 4)( 5x - 2 ) - 3( x - 4 ) = 0

( x + 2 )( x^2 - 2x + 4 ) + x( x + 5 )( x - 5 )

LD
16 tháng 9 2020 lúc 16:01

Lần sau bạn ghi đúng lớp ạ ~

( x - 4 )( 5x - 2 ) - 3( x - 4 ) = 0

⇔ 5x2 - 2x - 20x + 8 - 3x + 12 = 0

⇔ 5x2 - 25x + 20 = 0

⇔ 5x2 - 5x - 20x + 20 = 0

⇔ 5x( x - 1 ) - 20( x - 1 ) = 0

⇔ ( x - 1 )( 5x - 20 ) = 0

⇔ \(\orbr{\begin{cases}x-1=0\\5x-20=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=1\\x=4\end{cases}}\)

( x + 2 )( x2 - 2x + 4 ) + x( x + 5 )( x - 5 )

= x3 + 23 + x( x2 - 25 )

= x3 + 8 + x3 - 25x

= 2x3 - 25x + 8 

Bình luận (0)
 Khách vãng lai đã xóa

Các câu hỏi tương tự
NH
Xem chi tiết
NA
Xem chi tiết
H24
Xem chi tiết
H24
Xem chi tiết
HD
Xem chi tiết
NN
Xem chi tiết
PL
Xem chi tiết
DN
Xem chi tiết
NK
Xem chi tiết